Sintesis Dan Karakteristik MgSiO3 (Amorphous) dari Bittern dan Daun Bambu Dengan Metode Presipitasi dan Ekstraksi - Marela, Shanaz (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to synthesize and characterize amorphous magnesium silica from bittern and bamboo leaves using precipitation and extraction methods. Bittern is used as a source of magnesium and bamboo leaf ash as a source of silica. Synthesis was carried out by varying the volume of bittern (30-90 ml) and stirring speed (200-400 rpm). Characterization was carried out using XRF and XRD. The results showed that the optimum composition was obtained at a bittern volume of 90 ml and a stirring speed of 400 rpm with as content of 36,6% and MgO of 10,4%. The product showed an amorphous structure based on the result of XRD analysis. This study shows the potential of bittern and bamboo leaf waste as alternative raw materials for the production of amorphous magnesium silica.